Performing women : Gender, self, and representation in late medieval Metz - Crowder, Susannah (Book collections on Project MUSE., 2018)
This book takes on a key problem in the history of drama: the 'exceptional' staging of the life of Catherine of Siena by a female actor and a female patron in 1468 Metz. Exploring the lives and performances of these previously anonymous women, the book brings the elusive figure of the female performer to centre stage. It integrates new approaches to drama, gender and patronage with a performance methodology to explore how the women of fifteenth-century Metz enacted varied kinds of performance that extended beyond the theatre. For example, decades before the 1468 play, Joan of Arc returned from the grave in the form of an impersonator named Claude. Offering a new paradigm of female performance that positions women at the core of public culture, Performing women is essential reading for scholars of pre-modern women and drama, and is also relevant to lecturers and students of late-medieval performance, religion and memory